Pengaruh Social Media Marketing Activities terhadap Purchase Intention pada Theme Parks melalui Social Commerce - R. Naya Nirwasita; Gita Siswhara (SOSMANIORA: Jurnal Ilmu Sosial dan Humaniora, 2026)
The objective of this study is to analyze the effect of social media marketing activities on consumers’ purchase intentions toward theme parks, with social commerce serving as a mediating variable. The study employs a quantitative approach using an explanatory survey method. Data collection was conducted by distributing an online questionnaire to 240 respondents who actively use social media and have viewed content related to theme parks such as Dufan, Trans Studio Group, and Jatim Park Group. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with the assistance of SmartPLS. The findings revealed that social media marketing activities exert a positive and significant influence on purchase intention as well as social commerce. Social commerce was also found to have a positive effect on purchase intention and to mediate the relationship between social media marketing activities and purchase intention. These findings demonstrate that interactive social media marketing strategies supported by social commerce activities can increase consumer interest in purchasing tickets or visiting theme parks. Stimulus-Organism-Response (SOR) model is used as the theoretical foundation in this study.